Fine mapping of LrSV2, a race-specific adult plant leaf rust resistance gene on wheat chromosome 3BS - Diéguez, M. J. (2014)
Three leaf rust resistance genes were identified in the durable leaf rust resistant Argentinean wheat variety Sinvalocho MA: the seedling resistance gene Lr3 on distal 6BL and two adult plant resistance genes, LrSV1 and LrSV2, on chromosomes 2DS and 3BS, respectively. To develop a high-resolution genetic map for LrSV2, 10 markers were genotyped on 343 F2 individuals from a cross between Sinvalocho MA and Gama6. The closest co-dominant markers on both sides of the gene (3 microsatellites and 2 STMs) were analyzed on 965 additional F2s from the same cross. Microsatellite marker cfb5010 cosegregated with LrSV2 whereas flanking markers were found at 1 cM distal and at 0.3 cM proximal to the gene. SSR markers designed from the sequences of cv Chinese Spring BAC clones spanning the LrSV2 genetic interval were tested on the recombinants, allowing the identification of microsatellite swm13 at 0.15 cM distal to LrSV2. This delimited an interval of 0.45 cM around the gene flanked by the SSR markers swm13 and gwm533 at the subtelomeric end of chromosome 3BS.